Economic values for production and functional traits in Holstein cattle of Costa Rica - Vargas, B.; Groen, A.F.; Herrero, Mario; Arendonk, Johan A.M. van (Elsevier, 2002)
Economic values for production traits (carrier, fat, protein, and dressing percentage) and functional traits (conception rate, survival rate, body weight, and rumen capacity) were calculated for Holstein cattle of Costa Rica. Economic values were derived using a bio-economic model that combined genetic potential performance, feeding strategies and optimum culling and insemination policies to obtain actual phenotypic performance. Two evaluation bases were considered: fixed herd-size and fixed milk-output. With a fixed herd-size economic values were 0.04 (carrier), 5.25 (fat), 3.95 (protein), 0.92 (dressing percentage), 1.30 (conception rate), 2.42 (survival rate), 0.81 (body weight) and 84.53 (rumen capacity). With a milk-output limitation, economic values for all traits except survival rate were lower than for fixed herd-size. The respective values were −0.04, 3.53, 2.91, 0.88, 0.85, 3.18, 0.51 and 45.59. Sensitivity analysis indicated that economic values of fat, protein and rumen capacity increased significantly with higher prices of milk solids. Other traits were less sensitive to a change in price of milk solids. Changes in price of concentrate did not alter economic values significantly. Under a fixed feeding strategy, economic values for functional traits increased substantially, while those for production traits decreased. The results of this analysis suggest that genetic improvement of fertility, health and cow-efficiency traits will have a clear positive effect on profitability of Holstein cows in Costa Rica, especially when feeding conditions are not optimal.